Pengaruh Iklan Politik terhadap Persepsi Masyarakat dalam Pemilihan Legislatif dan Kepala Daerah di Kabupaten Kepulauan Tanimbar Kota Saumlaki Tahun 2022 - Johanis Nifan; Polikarpus Lalamafu; Olivir Srue (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Political advertising is an activity that is often carried out by politicians when welcoming a democratic party as can be seen from the perception of the whole community. The purpose of this research is to be able to determine the influence of political advertising on public perceptions of the Legislative and Regional Head election in the Tanimbar Islands District, Saumlaki City in 2022. The design of this study is to use a quantitative approach. The data used is primary data which is sourced directly from the community strata. Data collection techniques used in this research were interviews and questionnaires. The number of samples used in this research amounted to 200 samples. The data analysis technique that will be used is using simple linear regression analysis which will be assisted by using the SPSS 26 software. The results found in this research are the influence of political advertisements on people's perceptions of the Legislative and Regional Head elections in the Tanimbar Islands District, Saumlaki City in 2022.